Circulating DNA tumor fraction as a biomarker for advanced breast cancer - Cybulla, Emily; Stover, Daniel G. (Frontiers in Oncology, 2025)
Liquid biopsy has emerged as an important clinical tool for managing a range of tumor types, including advanced breast cancers. Early work in metastatic breast cancer (MBC) demonstrated that circulating tumor DNA (ctDNA) could be reliably detected in patient peripheral blood samples. These discoveries laid the groundwork for more recent work monitoring the circulating DNA tumor fraction, which is the fraction of ctDNA among total cell-free DNA. Studies have shown tumor fraction to be a useful prognostic biomarker in advanced breast cancer. Clinical trials have also begun to explore tumor fraction’s role in predicting response to specific therapeutic agents in MBC. Future investigation will be critical to understand when and how tumor fraction should inform clinical decision-making for breast cancer patients in a variety of settings, especially given the increasing accessibility of both commercial and research-based assays that report tumor fraction.